KP Tours (ATI records - full disclosure) - Piché, Justin; Ferguson, Matthew; Walby, Kevin (Université d'Ottawa | University of Ottawa, 2019)
In October 2013, Correctional Service Canada (CSC) decommissioned Kingston Penitentiary (KP) in Kingston, Ontario. To commemorate KP’s closing, CSC organized facility tours for staff members and their families, journalists, and the public. Based on an analysis of an Access to Information disclosure informed by Goffman’s (1959) conceptualization of impression management, we examine CSC’s backstage work integral to the organization of KP tours. Our analysis reveals how CSC sought to elevate positive stories of penitentiary staff, as well as the organization’s contribution to public safety and the local community as a means of neutralizing opposition to the closure of the facility expressed by stakeholders. We conclude by discussing the implications of carceral symbolism and the form it takes when punishment memorialization is driven by the imperatives of ‘correctional’ agencies.
Keywords: prison tourism; carceral symbolism; carceral retasking; Correctional Service Canada; Access to Information